2016
DOI: 10.1088/0964-1726/25/4/045022
|View full text |Cite
|
Sign up to set email alerts
|

A validated model for induction heating of shape memory alloy actuators

Abstract: Shape memory alloy (SMA) actuators deliver high forces while being compact and reliable, making them ideal for consideration in aerospace applications. One disadvantage of these thermally driven actuators is their slow cyclic time response compared to conventional actuators. Induction heating has recently been proposed to quickly heat SMA components. However efforts to date have been purely empirical. The present work approachs this problem in a computational manner by developing a finite element model of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Thus, it consequently leads to varying displacement on the tip of optic fiber at the free end due to a thermo-elastic effect. A sequence of potential difference has been applied with varying voltage, current, and frequency for obtaining their actuation response and to study its dynamic displacement characteristics during real-time experimentation (Potapov and Da Silva, 2000; Saunders et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it consequently leads to varying displacement on the tip of optic fiber at the free end due to a thermo-elastic effect. A sequence of potential difference has been applied with varying voltage, current, and frequency for obtaining their actuation response and to study its dynamic displacement characteristics during real-time experimentation (Potapov and Da Silva, 2000; Saunders et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In the following paper, the stress redistribution due to the phase transformation in notched cylindrical SMA specimens will be analyzed by utilizing the SMA constitutive model developed by Lagoudas et al (2012). This model has been utilized by a number of studies in order to predict the thermomechanical behavior of various SMA compositions and structures (Baxevanis et al, 2012; Hernandez et al, 2013; Masood et al, 2013; Saunders et al, 2016; Scalet et al, 2016; Teeriaho, 2013) and has shown generally good agreement when compared to experimental studies. For modeling purposes, the constitutive model utilized assumes that the phase transformation occurs in a decentralized manner, in that although the local crystal structure is either austenite or martensite, the model assumes that the crystallographic information is smeared out such that a martensitic volume fraction can be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Joule heating is a good candidate to decrease the heating time [2]. The induction heating has been evaluated for wires, as well as tubes in torsion and recently considered in the case of beams [3] but only in the case of small deformations (i.e. with linear strain-displacement equations).…”
Section: Introductionmentioning
confidence: 99%